Frequency of Helicobacter Pylori Infection Among Asymptomatic Adults Men With Sulfur Mustard Induced Respiratory Diseases in Iranian Veterans: C13-Urea Breathed Test With New Infrared Spectroscopy: A Case– Control Study - Agin, Khosrow; Nikpour, Shahriar (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Background: Helicobacter pylori (HP) infection is one of the commonest contaminations in the worldwide, and particularly in developing counties. It has found in a few of pulmonary disorders. However, the status of HP infection has not been known among the population of Sulfur Mustard(SM) induced respiratory diseases. The purpose of the study was to detect HP infection among asymptomatic SM focus population, and to compare with healthy subjects. Material and methods: Sample population sequentially enrolled based upon a self-reported questionnaire in chemical veteran’s clinic. The HP detected by C13-Urea breath test via infrared spectroscopy method. Results: The mean age was 46.17±9.21 SD in the case, and 46.27±9.18 SD in the control groups, respectively. The age ranged from 35 to 70 years. The prevalence rate of infection established in case 78.3% and in control groups 50.4%, respectively. the significant differences found between cases with control groups (χ<0.001). Conclusion: The significant difference observed between asymptomatic SM induced respiratory diseases with healthy subjects among Iranian veterans. Our results may be related to accruing of HP infection during wartime. Keywords: Helicobacter pylori, sulfur mustard gas, C13-urea breathe test, infrared spectroscopy, respiratory disease, war, asymptomatic, male, adults, Iranian.